209 Beta-catenin Functions as an Endogenous Negative Regulator of Endothelial Nitric Oxide Synthase Function. (31st May 2014) - Warboys, Christina; Chen, Nan; Ward, Jeremy; Ferro, Albert
Abstract : Introduction: Nitric oxide (NO) derived from endothelial NO synthase (eNOS) has multiple anti-atherogenic actions in the vasculature. eNOS activity is controlled by association with a number of regulatory proteins. We here investigated the possible existence of novel previously unrecognised protein associations with eNOS in endothelial cells, and the functional implications of this. Methods and results: Analysis of eNOS immunoprecipitates by mass spectroscopy identified β-catenin as a novel binding partner of eNOS in human umbilical vein endothelial cells (HUVEC). This previously unrecognised interaction was confirmed in situ using a proximity ligation assay. We also found, through western blotting of HUVEC nuclear lysates and immunostaining of fixed HUVEC, that activation of eNOS using several different agonists (adenosine, salbutamol, histamine or thrombin), or application of an NO donor (spermine NONOate) or 8-bromo-cGMP increased nuclear translocation of β-catenin. We also observed that expression of the β-catenin target genes, cyclin D1 and interleukin-8, were increased following exposure to spermine NONOate or sildenafil (which acts to increase cGMP) relative to vehicle using quantitative real-time PCR (cyclin D1 P < 0.05 for both; IL-8 P < 0.05 and P < 0.001 respectively; n = 4). We next investigated the role of β-catenin in regulating eNOS activity using wild type and β-catenin -/- mouse pulmonary endothelial cells (MPECs). We assessed NO bioactivity in both cell types by analysing levels of cGMP (a surrogate marker of NO production) using a cGMP ELISA. cGMP (pmol/mg protein) was significantly increased in β-catenin -/- MPECs compared to wild type MPECs (P < 0.05, n = 5) indicative of increased NO production and thus increased eNOS activity. eNOS is classically activated by phosphorylation of Ser1177 which we evaluated by western blotting with an antibody specific for eNOS phosphorylated on this residue. eNOS phosphorylation was significantly greater in β-catenin -/- MPECs when compared to wild type cells (P < 0.01, n = 6). Whilst adenosine and histamine increased phosphorylation in wild type MPECs there was no further increase in phosphorylation observed in β-catenin -/- MPECs. We also found that eNOS phosphorylation was abrogated following pre-treatment with an Akt inhibitor in wild type MPECs following treatment with vehicle, adenosine or histamine (P < 0.05, P < 0.005 and P < 0.005 respectively, n = 6), however it was only partially reduced by the Akt inhibitor in β-catenin -/- MPECs (n = 6). Conclusions: Loss of β-catenin increases eNOS phosphorylation and activity, in part via Akt. We conclude therefore that β-catenin functions as an endogenous negative regulator of eNOS activity in endothelial cells. We also provide evidence for bidirectional communication between eNOS and β-catenin signalling pathways. Further work will address the physiological importance of this cross-talk between two key regulators of endothelial function.